Posted by **Anonymous** on Monday, September 26, 2011 at 12:20pm.

Kahlil said that using the equation

€

(a + b)2 = a2 + 2ab + b2, , he can find a

similar equation for

€

(a − b)2 . Examine his argument. If it is correct, supply any

missing steps or justification; If it is incorrect point out why.

€

(a + b)2 = [a + (−b)]2

= a2 + 2a(−b) + (−b)2

= a2 − 2ab + b2

Mathematical Connections 5‐3

2. a.

## Answer This Question

## Related Questions

- math 213 - Kahlil said that using the equation he can find a similar equation ...
- math - Kahlil said that using the equation (a + b)2 = a2 + 2ab + b2, he can find...
- math - Hosni gave the following argument that -(a+b)=-a+-b for all integers a ...
- Math - Hosni gave the following argument that -(a + b) = -a + -b, for all ...
- math - 42. Hosni gave the following argument that 2(a 1 b) 5 2a 1 2b, for all ...
- algebra - Hosni gave the following argument that 2(a 1 b) 5 2a 1 2b, for all ...
- Algebra - Why does this happen? A=3 and b=2 A+b=c is the equation. Multiplying ...
- Math - Equation of the circle - Find an equation of the circle whose endpoints ...
- Algebra - Find the missing coordinate to complete the ordered-pair solution to ...
- calculus - Find an equation for the surface consisting of all points P(x, y, z) ...

More Related Questions